Development on multiband patch antenna for terahertz applications - Weng, ZhiLong (Nanyang Technological University, 2024)
In this project, we will be developing a multiband patch antenna optimized for terahertz frequencies, focusing on the sub-THz range of 0.3 to 0.5 THz. The study primarily utilized copper as the patch material due to its favorable properties at THz frequencies. Two methods were explored for achieving multiband capabilities: the dual-substrate method, incorporating Silicon Germanium as a secondary substrate, and the stepped-impedance method, with the latter showing promising results. Through Computer Simulation Technology (CST) simulations, the stepped-impedance method demonstrated significant performance, enabling precise control over design of multiband operation that based on the fundamental 0.5 THz dipole patch design and efficient impedance matching. This approach offers significant advancements for THz communication technologies, suggesting a pathway for high-speed, wide-bandwidth applications.